2013
DOI: 10.1002/2013ja018997
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the propagation characteristics of large‐scale traveling ionospheric disturbances using ground‐based and satellite data

Abstract: In this article, the propagation characteristics of large‐scale traveling ionospheric disturbances (LS TIDs) are estimated during the geomagnetic storm periods of 14–16 May 2005 and 25–27 September 2011 over South Africa. One and two GPS arrays have been independently considered for the storms of 15 May 2005 and 26 September 2011, respectively. The average periods of dominant modes (≈ 2.5–3.5h) in the time series data were determined by applying wavelet analysis on both ionosonde and GPS data. The consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 36 publications
(75 reference statements)
0
40
0
Order By: Relevance
“…Different methods have been used to detrend TEC to identify TID in TEC perturbations. For example polynomial fitting (Katamzi et al, 2012;Habarulema et al, 2013a) and moving average (Hernández-Pajares et al, 2006) have all performed quite well. Without introducing artificial periodicities in the TEC data, we applied a least square polynomial fit of degree 6 to the vTEC.…”
Section: Procedures For Identifying the Wave-like Structuresmentioning
confidence: 99%
“…Different methods have been used to detrend TEC to identify TID in TEC perturbations. For example polynomial fitting (Katamzi et al, 2012;Habarulema et al, 2013a) and moving average (Hernández-Pajares et al, 2006) have all performed quite well. Without introducing artificial periodicities in the TEC data, we applied a least square polynomial fit of degree 6 to the vTEC.…”
Section: Procedures For Identifying the Wave-like Structuresmentioning
confidence: 99%
“…Analyses of these two storm events by other investigators also indicated very similar pattern at various locations around the globe. Ionosonde observations in the South African sector [ Habarulema et al , ] on 26 September 2011 show that TID signatures only started to appear at ∼18:00 UT, and no sign of significant oscillations in the ionosphere had been observed since the SSC (∼12:30 UT) until ∼18:00 UT. For the 24/25 October 2011 storm, ionosonde data from S.J.…”
Section: Physical Mechanismmentioning
confidence: 99%
“…Likewise, the calculated scale size of the observed SS-TECP appears to be significantly larger than the typical wavelength of most ionospheric disturbances. The propagation speed and wavelength of LSTIDs are generally found in the range of 100-1000 m/s and 600-3000 km [see, e.g., Nicolls et al, 2004;Lee et al, 2008;Ding et al, 2008;Habarulema et al, 2013]. There are a few types of disturbances in high-latitude ionosphere (mainly from all-sky airglow measurements) that do propagate at a speed of several km/s, such as the westward traveling surge [Akasofu, 1964;Kan et al, 1984] or the longitudinally propagating arc waves reported by Uritsky et al [2009].…”
Section: Physical Mechanismmentioning
confidence: 99%
“…Hernández-Pajares et al (2011) provided ionospheric monitoring based on GNSS measurements and assessed TIDs, solar flares, ionospheric storms and scintillation. Habarulema et al (2013) estimated the propagation characteristics of large-scale TIDs (LSTIDs) during geomagnetic storm, and showed that disturbances were mostly propagating nearly equatorward. Ding et al (2014) comparatively investigated ionospheric disturbances over North America and China based on GPS dense regional observations.…”
Section: Introductionmentioning
confidence: 99%